Pengaruh Social Media Marketing, Perceived Value, Perceived Quality, Brand Image, Dan Customer Satisfaction Terhadap Behavior Intention Pada Fastfood Restaurant di Kota Batam - Lady Lady; Jusvenny Jusvenny (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The development of globalization affects people in various aspects of life. One of them is the fast-food industry, people prefer to eat at fast-food restaurants where food is prepared and served quickly. The increasing growth of fast-food restaurants causes strong competition between fast-food restaurants. The purpose of this study is to develop and test a framework to investigate the significant effect between social media marketing, perceived value, perceived quality, and behaviour intention and the intervening effect of the brand image and customer satisfaction in fast-food restaurants in Batam. The respondents in this study are customers who have visited the top five popular fast-food restaurants in Batam. The sample’s criteria used in this study is non-probability with judgemental sampling method. A total of 250 questionnaires were returned and the data were analyzed using SEM (Structural Equation Modelling) PLS. The results of this study indicate that social media marketing has a significant effect to brand image, perceived quality, and perceived value have a significant effect on customer satisfaction, brand image and customer satisfaction have a significant effect on behaviour intention.